Retinal changes in patients with angina pectoris and anginal equivalents: a study of patients with normal coronary angiography - Eslami Vahid; Mojahedin Simin; Nourinia Ramin; Tabary Mohammadreza; Khaheshi Isa (Sciendo, 2021)
Background and aims. Approximately 10-30% of the patients with typical symptoms of angina pectoris have normal angiography showing normal macrovasculature. In these patients, however, the microvascular problems should be monitored. Hence, the main aim of this study is to evaluate retinal changes in normal angiographic patients.